Porous Se@SiO2 Nanoparticles Enhance Wound Healing by ROS-PI3K/Akt Pathway in Dermal Fibroblasts and Reduce Scar Formation - Yang, Bo-Yu; Zhou, Zhi-Yuan; Liu, Shi-Yun; Shi, Ming-Jun; Liu, Xi-Jian; Cheng, Tian-Ming; Deng, Guo-Ying; Tian, Ye; Song, Jian; Li, Xuan-Hao (Frontiers in Bioengineering and Biotechnology, 2022)
Hypertrophic scarring, which is characterized by excessive extracellular matrix (ECM) deposition and abnormal fibroblast homeostasis, is an undesirable outcome of dermal wound healing. Once formed, the scar will replace the normal function of local skin, and there are few noninvasive clinical treatments that can cure it. Se@SiO2 nanoparticles (NPs) were synthesized to suppress oxidative stress, which induced the presence and activation of myofibroblasts during wound recovery. The characterization, antioxidant capacity and biological safety of Se@SiO2 NPs were evaluated. A full-thickness excisional wound model was established, and the wounds were divided into three groups. The re-epithelization and distribution of collagen fibers were assessed using hematoxylin and eosin staining and Masson’s trichome staining after specific treatments. Our results revealed that the Se@SiO2 NPs accelerated dermal wound healing and suppressed the formation of hypertrophic scars, accompanied by oxidative stress inhibition. Moreover, we found that Se@SiO2 NPs worked by activating the PI3K/Akt pathway and upregulating the phosphorylation of Akt. The findings of our study provide a new method to promote dermal scar-free wound healing by suppressing excessive oxidative stress and through PI3K/Akt pathway activation.